Onion bulb production through bulblets for enhancing farmers’ income - Gupta, P K; Tiwari, S K; Jankiram, T (Indian Horticulture, 2023)
Onion is one of the most important vegetable and spice crops grown throughout the country. It is consumed raw, cooked, fried, dried or roasted. Besides being used as food, onions have a variety of medicinal properties. It has high export potential also. The higher nutritive value, several medicinal properties and vast export potential have boosted the scope of the crop.